Exploiting advantages of empirical and optimization approaches to design alkali activated materials in a more efficient way. (19th July 2021) - Kočí, Václav; Koňáková, Dana; Pommer, Vojtěch; Keppert, Martin; Vejmelková, Eva; Černý, Robert
Highlights: Alternative approach to current optimum mix design techniques is proposed. Oriented extension of empirical design using downhill simplex method is used. In two optimization steps the best result of empirical approach is improved by 40% Material characterization techniques are used to understand the difference. Selected functional parameters are determined and compared with ordinary concrete. Abstract: The alkaline activation of aluminosilicates represents an alternative to cement based materials, which has many benefits, the environmental in particular. The mix design is though, as compared with the concrete mixtures, still less advanced as different principles are to be applied. Empirical approaches, that are usually employed, can exploit designers' experience, but they are not as effective yet as they could be. Taking advantages of this experience, this paper extends the empirical design using a straightforward optimization technique. Such a combination is predisposed to significantly reduce the number of optimization steps, making thus possible to find the optimum quickly and effectively. At the application of the combined approach, the optimization of alkali activated material made of ceramic powder, sodium hydroxide, water glass and siliceous sand is performed, in order to reach the highest compressive strength within a defined workability. In only two optimization steps, the best result of the empirical approach is improved by 40%, introducing a material with the compressive strength of 34.6 and 45.9 MPa after 7 and 28 days, respectively. The designed alkali activated aluminosilicate is then, together with the less successful mixes, subjected to a detailed characterization of microstructure, texture and composition to explain and understand the fundaments of the progress made. Finally, selected functional parameters are determined and compared with the properties of ordinary concrete to get a complex overview of the developed material.